Microbial Greenhouse Gas Dynamics Associated With Warming Coastal Permafrost, Western Canadian Arctic - Lapham, Laura L.; Dallimore, Scott R.; Magen, Cédric; Henderson, Lillian C.; Powers, Leanne C.; Gonsior, Michael; Clark, Brittany; Côté, Michelle; Fraser, Paul; Orcutt, Beth N. (Frontiers in Earth Science, 2020)
Permafrost sediments contain one of the largest reservoirs of organic carbon on Earth that is relatively stable when it remains frozen. As air temperatures increase, the shallow permafrost thaws which allows this organic matter to be converted into potent greenhouse gases such as methane (CH4) and carbon dioxide (CO2) through microbial processes. Along the Beaufort Sea coast in the vicinity of the Tuktoyaktuk Peninsula, Northwest Territories, Canada, warming air temperatures are causing the active layer above permafrost to deepen, and a number of active periglacial processes are causing rapid erosion of previously frozen permafrost. In this paper, we consider the biogeochemical consequences of these processes on the permafrost sediments found at Tuktoyaktuk Island. Our goals were to document the in situ carbon characteristics which can support microbial activity, and then consider rates of such activity if the permafrost material were to warm even further. Samples were collected from a 12 m permafrost core positioned on the top of the island adjacent to an eroding coastal bluff. Downcore CH4, total organic carbon and dissolved organic carbon (DOC) concentrations and stable carbon isotopes revealed variable in situ CH4 concentrations down core with a sub-surface peak just below the current active layer. The highest DOC concentrations were observed in the active layer. Controlled incubations of sediment from various depths were carried out from several depths anaerobically under thawed (5°C and 15°C) and under frozen (−20°C and −5°C) conditions. These incubations resulted in gross production rates of CH4 and CO2 that increased upon thawing, as expected, but also showed appreciable production rates under frozen conditions. This dataset presents the potential for sediments below the active layer to produce potent greenhouse gases, even under frozen conditions, which could be an important atmospheric source in the actively eroding coastal zone even prior to thawing.